KEMAMPUAN NUMERASI AND NEWMAN PROCEDURE: ANALISIS KESALAHAN MAHASISWA CALON GURU SD DALAM MENYELESAIKAN MASALAH MATEMATIKA - Iva Nurmawanti; Vivi Rahmatul Hidayati; Hikmah Ramdhani Putri; Mega Puspita Sari (LPPM Universitas Bina Bangsa, 2023)
Numeracy is an essential skill that must be possessed to be successful in the 21st century. Numeration contains complex problems that link mathematics to everyday life. It is necessary to know the numeracy abilities of prospective elementary school teacher students as an initial effort to develop the numeracy abilities of future elementary school teachers. Apart from that, knowing what errors arise in solving numeracy questions is necessary to know what actions to use to develop the numeracy of prospective elementary school teachers. One theory that can be used to see student errors in solving numeracy questions is based on Newman's Errors Analysis (NEA). This research used a qualitative approach involving 154 students, of which 124 experienced errors. The research results showed that there were student errors in Reading Errors (R) at 9.68%, Comprehension Errors (C) at 27.42%, Transformation Errors (T) at 22.58%, Process Skills Errors (P) at 35, 48%, and Encoding Errors (E) of 4.84%. These errors are caused by students not being able to understand the basic concept of fractions, incorrect conceptual understanding regarding the concept of fractions, and students not understanding how to write fraction symbols and what two fractions have in common